What to ask the person in the mirror : critical questions for becoming a more effective leader and reaching your potential - Kaplan, Robert Steven (Boston, Mass. : Harvard Business Review Press, 2011)
Great leadership is not about having all the answers- it is, more often, about having the courage to ask the critical questions. In What to Ask the Person in the Mirror, Robert Kaplan offers a concise and engaging guide to help executives improve their effectiveness as leaders. At the core of the book is a series of critical questions to help you lead your organization more successfully and take ownership of your career.--[book jacket]
Vision and priorities -- Managing your time -- Giving and getting feedback -- Succession planning and delegation -- Evaluation and alignment -- The leader as role model -- Reaching your potential -- Bringing it all together.
Includes bibliographical references (pages [245]-247) and index.
Description based on print version record.
Keywords: Leadership; Executive ability; Executive ability; Leadership; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books